A hardware in the loop simulation testbed for vision-based leader-follower formation flight. (November 2017) - Dehghani, Mohammad A.; Menhaj, Mohammad B.; Ghaderi, Hadi
Abstract: This paper proposes a hardware in the loop simulation testbed by using airborne seekers (an onboard visual tracking system) as a relative measurement sensor in the leader-follower formation flight. To the best of the authors' knowledge, this is the first study on experimental applications of airborne seekers in unmanned aircraft formation flight. The proposed structure gives an effective method to study the effects of uncertainties such as the camera process delay and the seeker measurement noises on formation keeping. Compensation of errors in visual measurements is considered as well.